Social Justice and Critical Pedagogy in the Literature Classroom: Reading Matilda with Student Teachers - Marie (CLELEjournal, 2023)
The first article reports on a study in teacher education in Sweden on the potential of Roald Dahl's Matilda for teaching about social class prejudice, as well as critical literacy, social justice and inclusion. The paper reveals important issues around childhood reading for student teachers and their future students.